Tensiones entre la observación participante y la participación militante: la reflexividad como parte del trabajo etnográfico en un movimiento socioterritorial - Isidro, Maria Eugenia (2018)
In this work some refl ections are exposed that arise from the realization of an ethnography in a socioterritorial movement of environmental character that resists the current agrarian model in a medium-sized Argentine city. In addition to conducting a brief tour of theoretical concepts central to research such as "socio-territorial movements" and "identity", we are dedicated to unraveling the details of ethnographic work describing in detail the implementation of the techniques used (observation participant and interviews), their potential and risks. At the same time, we deepened the tensions that were faced during the research process, while emphasizing refl exivity as an essential tool of the social researcher.